Answer:
x = -3 , y = 2 thus D) is your answer
Step-by-step explanation by substitution:
Solve the following system:
{-9 = x - 3 y
6 - 2 x = 6 y
Hint: | Choose an equation and a variable to solve for.
In the first equation, look to solve for x:
{-9 = x - 3 y
6 - 2 x = 6 y
Hint: | Reverse the equality in -9 = x - 3 y in order to isolate x to the left hand side.
-9 = x - 3 y is equivalent to x - 3 y = -9:
{x - 3 y = -9
6 - 2 x = 6 y
Hint: | Solve for x.
Add 3 y to both sides:
{x = 3 y - 9
6 - 2 x = 6 y
Hint: | Perform a substitution.
Substitute x = 3 y - 9 into the second equation:
{x = 3 y - 9
6 - 2 (3 y - 9) = 6 y
Hint: | Expand the left hand side of the equation 6 - 2 (3 y - 9) = 6 y.
6 - 2 (3 y - 9) = (18 - 6 y) + 6 = 24 - 6 y:
{x = 3 y - 9
24 - 6 y = 6 y
Hint: | Choose an equation and a variable to solve for.
In the second equation, look to solve for y:
{x = 3 y - 9
24 - 6 y = 6 y
Hint: | Isolate y to the left hand side.
Subtract 6 y + 24 from both sides:
{x = 3 y - 9
-12 y = -24
Hint: | Solve for y.
Divide both sides by -12:
{x = 3 y - 9
y = 2
Hint: | Perform a back substitution.
Substitute y = 2 into the first equation:
Answer: {x = -3 , y = 2